Menghidupkan Kembali Semangat Hidup Berpancasila di Era Milenial - Maria Felsita Eno Wou; Advensiana Nono; Maria Bellcia Ruda; Klementian Ye Meo; Florentina Dasilfa Bhoko; Maria Bergita Bhoko (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This research aims to revive the spirit of Pancasila life in the millennial era. The research method used is a qualitative descriptive research method where data is collected through literature review. The literature used in this research is scientific articles related to reviving the spirit of Pancasila in the millennial era. Data collection was carried out by searching for articles from electronic journals and other publications related to the study topic. From the results of the study it can be seen It is concluded that reviving the spirit of Pancasila life in the millennial era is a rare strategy to maintain the integrity of the nation amidst the challenges of globalization, technological developments and shifting social values. Formal and informal education is the main key to instilling values. Pancasila. Implementation of values ​​such as tolerance, justice, mutual cooperation, and love of the country must be carried out through a creative approach that is in line with the characteristics of the millennial generation, such as through digital media, collaborative activities, and example. Therefore, there needs to be more awareness sign height.